Sodium-ion battery composite negative electrode material and battery

By using phenolic resin and polyacrylonitrile as precursors in sodium ion batteries, the problem of insufficient conductivity and cycle stability of the negative electrode material of sodium ion batteries is solved, and higher electrochemical performance and better Long battery life.

CN119133386APending Publication Date: 2024-12-13ZHONGKE RONNENG (YANCHENG) TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411154657.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-22
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing sodium ion battery anode materials have shortcomings in conductivity and cycle stability, which limits their commercialization process.

Method used

A composite material of soft carbon material and hard carbon material is used. The precursor of soft carbon material is phenolic resin, and the precursor of hard carbon material is polyacrylonitrile. A composite material with excellent conductivity and structural stability is formed through carbonization and composite treatment. and heat treatment and surface modification to optimize performance.

Benefits of technology

It significantly improves the conductivity and cycle stability of the composite material, extends the cycle life of the battery, and shows excellent electrochemical properties in specific capacity and rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133386A_ABST
    Figure CN119133386A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium ion battery composite negative electrode material which is formed by compounding a soft carbon material and a hard carbon material according to a certain proportion, a precursor of the soft carbon material is an organic matter which is high in phenolic resin carbon content and easy to carbonize, a precursor of the hard carbon material is a high-molecular polymer, the high-molecular polymer is polyacrylonitrile, and the high-molecular polymer is silicon dioxide. The invention relates to the technical field of electrochemical energy storage. According to the sodium ion battery composite negative electrode material and the battery, the soft carbon material has relatively large carbon layer size and relatively wide interlayer spacing and shows excellent conductivity, the hard carbon material has a compact carbon layer structure and stable chemical properties and is excellent in cycle performance, and by adjusting the ratio of the soft carbon to the hard carbon, the cycle performance of the sodium ion battery is improved. The comprehensive performance of the composite material can be optimized, the conductivity of the composite material is remarkably improved by adding the soft carbon material, rapid transmission of electrons in the negative electrode material is promoted, and the stable structure of the hard carbon material provides good support for the composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochemical energy storage, and in particular to a sodium ion battery composite negative electrode material and a battery. Background Art

[0002] Sodium-ion batteries are secondary batteries that rely on the movement of sodium ions between the positive and negative electrodes to complete charging and discharging. Their working principle is similar to that of the widely used lithium-ion batteries. The positive electrode of sodium-ion batteries usually uses vanadate materials, while the negative electrode uses carbon materials or vanadium oxides. When charging, sodium ions migrate from the positive electrode to the negative electrode and embed in the carbon or vanadium oxide at the negative electrode. When discharging, sodium ions are released from the negative electrode and return to the positive electrode, releasing the stored energy at the same time. Compared with lithium-ion batteries, sodium-ion batteries have the following advantages: (1) Sodium salt raw materials are abundant and inexpensive. The use of iron-manganese-nickel-based positive electrode materials is more convenient than lithium-ion batteries. (1) Due to the characteristics of sodium salt, it is possible to use low-concentration electrolyte (for the same concentration of electrolyte, the conductivity of sodium salt is about 20% higher than that of lithium electrolyte) to reduce costs; (2) Due to the characteristics of sodium salt, it is possible to use low-concentration electrolyte (for the same concentration of electrolyte, the conductivity of sodium salt is about 20% higher than that of lithium electrolyte) to reduce costs; (3) Sodium ions do not form alloys with aluminum, and aluminum foil can be used as the negative electrode current collector, which can further reduce costs by about 8% and weight by about 10%; (4) Due to the sodium ion battery's no over-discharge characteristic, it is possible to discharge sodium ion batteries to zero volts. The energy density of sodium ion batteries is greater than 100Wh / kg, which is comparable to lithium iron phosphate batteries, but its cost advantage is obvious, and it is expected to replace traditional lead-acid batteries in large-scale energy storage.

[0003] With the continuous growth of global demand for renewable energy, efficient and low-cost energy storage technology has become a research hotspot. Sodium-ion batteries are considered to be an important supplement to lithium-ion batteries due to their abundant resources and low costs. However, the current negative electrode materials of sodium-ion batteries still have deficiencies in conductivity and cycle stability, which limits their commercialization process. Therefore, the development of new high-performance negative electrode materials is of great significance to promoting the development of sodium-ion batteries. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a sodium ion battery composite negative electrode material and a battery, which solves the problems mentioned in the above background technology.

[0005] To achieve the above objectives, the present invention is implemented through the following technical scheme: a sodium ion battery composite negative electrode material, which is composed of a soft carbon material and a hard carbon material in a certain proportion. The precursor of the soft carbon material is a phenolic resin with a high carbon content and an organic matter that is easy to carbonize. The precursor of the hard carbon material is a polymer, and the polymer is polyacrylonitrile.

[0006] Preferably, the method for preparing a composite negative electrode material for a sodium ion battery comprises the following steps:

[0007] S1. Material selection and pretreatment:

[0008] (1) Soft carbon material precursor: Select phenolic resin with high carbon content and easy to carbonize organic matter as the precursor of soft carbon material. The precursor can form a soft carbon material with excellent conductivity during the carbonization process;

[0009] (2) Precursor of hard carbon material: A high molecular weight polymer is selected as the precursor of the hard carbon material. After high temperature carbonization, the precursor can form a hard carbon material with stable structure and excellent cycle performance;

[0010] (3) Pretreatment: Perform necessary pretreatment on the selected precursor, including cleaning, drying, crushing, etc., to ensure its purity and uniformity;

[0011] S2. Carbonization and compounding:

[0012] (1) Carbonization of soft carbon materials: The pretreated soft carbon material precursor is placed in a high-temperature furnace under inert atmosphere protection for carbonization treatment. The carbonization temperature is generally controlled at 600-1200°C.

[0013] (2) Carbonization of hard carbon materials: The pretreated hard carbon material precursor is placed in a high-temperature furnace under inert atmosphere protection for carbonization treatment. The carbonization temperature is generally controlled at 900-1500°C.

[0014] (3) Soft and hard carbon composite: the carbonized soft carbon material and the hard carbon material are mixed in a predetermined ratio, and physical methods such as ball milling and stirring are used in the mixing process. The ball milling speed is 200 to 500 r / min, and the ball milling time is 3 to 10 hours to obtain a matrix material with uniform particle size distribution and fine particles, and ensure that the two are evenly mixed. An appropriate amount of surfactant is added, and the composite material is further processed and heated;

[0015] S3, post-processing and performance optimization:

[0016] (1) Heat treatment: The composite material is placed in a high temperature furnace for heat treatment, and the temperature is generally controlled at 600-1200°C to further stabilize its structure and improve cycle stability;

[0017] (2) Surface modification: The surface of the composite material is modified by chemical treatment to improve its wettability with the electrolyte and ion transfer efficiency;

[0018] (3) Performance testing: Conduct electrochemical performance testing on the prepared soft and hard carbon composite negative electrode materials, including evaluation of indicators such as specific capacity, cycle stability, and rate performance, and optimize and adjust the preparation process based on the test results.

[0019] Preferably, in S2(1), nitrogen is used as the inert atmosphere, and the specific carbonization temperature is adjusted according to the type of precursor and the required carbon layer size and interlayer spacing.

[0020] Preferably, in S2(2), for the high molecular weight polymer precursor, its structural evolution during the pyrolysis process needs to be considered to ensure that the hard carbon material finally formed has the desired properties.

[0021] Preferably, a surfactant is added to S2(3) to improve the stability and dispersibility of the composite material, and the heating treatment is performed to optimize its electrochemical performance.

[0022] Preferably, in S3(2), the chemical treatment method is acid washing or alkali washing.

[0023] The invention also discloses a sodium ion battery, which is prepared by using the composite negative electrode material and the preparation method.

[0024] Beneficial Effects

[0025] The present invention provides a sodium ion battery composite negative electrode material and a battery. Compared with the prior art, the composite negative electrode material of the sodium ion battery has the following beneficial effects: the composite negative electrode material of the sodium ion battery is composited by a soft carbon material and a hard carbon material in a certain ratio, the precursor of the soft carbon material is selected from a phenolic resin organic matter with a high carbon content and easy to carbonize, the precursor of the hard carbon material is selected from a polymer, and the polymer is polyacrylonitrile, the soft carbon material has a large carbon layer size and a wide interlayer spacing, and exhibits excellent electrical conductivity, the hard carbon material has a dense carbon layer structure and stable chemical properties, and has excellent cycle performance, and the comprehensive performance of the composite material can be optimized by adjusting the ratio of soft carbon and hard carbon, the addition of soft carbon material significantly improves the electrical conductivity of the composite material, and promotes the rapid transmission of electrons in the negative electrode material, the stable structure of the hard carbon material provides good support for the composite material, effectively prevents the structural collapse of the negative electrode material during the charge and discharge process, and prolongs the cycle life of the battery, and the synergistic effect of the soft and hard carbon composite material makes it exhibit better electrochemical performance than a single carbon material in terms of specific capacity and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a flow chart of the steps of the present invention. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] See also Figure 1 The present invention provides three technical solutions: a composite negative electrode material for a sodium ion battery, which is composed of a soft carbon material and a hard carbon material in a certain proportion. The precursor of the soft carbon material is a phenolic resin, which is an organic matter with a high carbon content and is easy to carbonize. The precursor of the hard carbon material is a high molecular polymer, and the high molecular polymer is polyacrylonitrile.

[0029] The present invention also discloses a method for preparing a composite negative electrode material for a sodium ion battery, which specifically includes the following embodiments:

[0030] Embodiment 1

[0031] S1. Material selection and pretreatment:

[0032] (1) Soft carbon material precursor: Select phenolic resin with high carbon content and easy to carbonize organic matter as the precursor of soft carbon material. The precursor can form a soft carbon material with excellent conductivity during the carbonization process;

[0033] (2) Precursor of hard carbon material: A high molecular weight polymer is selected as the precursor of the hard carbon material. After high temperature carbonization, the precursor can form a hard carbon material with stable structure and excellent cycle performance;

[0034] (3) Pretreatment: Perform necessary pretreatment on the selected precursors, such as cleaning, drying, and crushing, to ensure their purity and uniformity;

[0035] S2. Carbonization and compounding:

[0036] (1) Carbonization of soft carbon materials: The pretreated soft carbon material precursor is placed in a high-temperature furnace under inert atmosphere protection for carbonization treatment. The carbonization temperature is generally controlled at 900°C.

[0037] (2) Carbonization of hard carbon materials: The pretreated hard carbon material precursor is placed in a high-temperature furnace under inert atmosphere protection for carbonization treatment. The carbonization temperature is generally controlled at 1200°C.

[0038] (3) Soft and hard carbon composite: The carbonized soft carbon material and the hard carbon material are mixed in a predetermined ratio. Physical methods such as ball milling and stirring are used in the mixing process. The ball milling speed is 350 r / min and the ball milling time is 7 hours to obtain a matrix material with uniform particle size distribution and fine particles. The two are ensured to be evenly mixed. A surfactant is added. The composite material is further processed and heated.

[0039] S3, post-processing and performance optimization:

[0040] (1) Heat treatment: The composite material is placed in a high-temperature furnace for heat treatment, and the temperature is generally controlled at 900°C to further stabilize its structure and improve cycle stability;

[0041] (2) Surface modification: The surface of the composite material is modified by chemical treatment to improve its wettability with the electrolyte and ion transfer efficiency;

[0042] (3) Performance testing: Conduct electrochemical performance testing on the prepared soft and hard carbon composite negative electrode materials, including evaluation of indicators such as specific capacity, cycle stability, and rate performance, and optimize and adjust the preparation process based on the test results.

[0043] Embodiment 2

[0044] S1. Material selection and pretreatment:

[0045] (1) Soft carbon material precursor: Select phenolic resin with high carbon content and easy to carbonize organic matter as the precursor of soft carbon material. The precursor can form a soft carbon material with excellent conductivity during the carbonization process;

[0046] (2) Precursor of hard carbon material: A high molecular weight polymer is selected as the precursor of the hard carbon material. After high temperature carbonization, the precursor can form a hard carbon material with stable structure and excellent cycle performance;

[0047] (3) Pretreatment: Perform necessary pretreatment on the selected precursors, such as cleaning, drying, and crushing, to ensure their purity and uniformity;

[0048] S2. Carbonization and compounding:

[0049] (1) Carbonization of soft carbon materials: The pretreated soft carbon material precursor is placed in a high-temperature furnace under inert atmosphere protection for carbonization treatment. The carbonization temperature is generally controlled at 1200°C.

[0050] (2) Carbonization of hard carbon materials: The pretreated hard carbon material precursor is placed in a high-temperature furnace under inert atmosphere for carbonization treatment. The carbonization temperature is generally controlled at 1500°C.

[0051] (3) Soft and hard carbon composite: The carbonized soft carbon material and the hard carbon material are mixed in a predetermined ratio. Physical methods such as ball milling and stirring are used in the mixing process. The ball milling speed is 500 r / min and the ball milling time is 10 hours to obtain a matrix material with uniform particle size distribution and fine particles. The two are ensured to be evenly mixed. A surfactant is added. The composite material is further processed and heated.

[0052] S3, post-processing and performance optimization:

[0053] (1) Heat treatment: The composite material is placed in a high temperature furnace for heat treatment, and the temperature is generally controlled at 1200°C to further stabilize its structure and improve cycle stability;

[0054] (2) Surface modification: The surface of the composite material is modified by chemical treatment to improve its wettability with the electrolyte and ion transfer efficiency;

[0055] (3) Performance testing: Conduct electrochemical performance testing on the prepared soft and hard carbon composite negative electrode materials, including evaluation of indicators such as specific capacity, cycle stability, and rate performance, and optimize and adjust the preparation process based on the test results.

[0056] Embodiment 3

[0057] S1. Material selection and pretreatment:

[0058] (1) Soft carbon material precursor: Select phenolic resin with high carbon content and easy to carbonize organic matter as the precursor of soft carbon material. The precursor can form a soft carbon material with excellent conductivity during the carbonization process;

[0059] (2) Precursor of hard carbon material: A high molecular weight polymer is selected as the precursor of the hard carbon material. After high temperature carbonization, the precursor can form a hard carbon material with stable structure and excellent cycle performance;

[0060] (3) Pretreatment: Perform necessary pretreatment on the selected precursors, such as cleaning, drying, and crushing, to ensure their purity and uniformity;

[0061] S2. Carbonization and compounding:

[0062] (1) Carbonization of soft carbon materials: The pretreated soft carbon material precursor is placed in a high-temperature furnace under inert atmosphere protection for carbonization treatment. The carbonization temperature is generally controlled at 600°C.

[0063] (2) Carbonization of hard carbon materials: The pretreated hard carbon material precursor is placed in a high-temperature furnace under inert atmosphere protection for carbonization treatment. The carbonization temperature is generally controlled at 900°C.

[0064] (3) Soft and hard carbon composite: The carbonized soft carbon material and the hard carbon material are mixed in a predetermined ratio. Physical methods such as ball milling and stirring are used in the mixing process. The ball milling speed is 200 r / min and the ball milling time is 3 hours to obtain a matrix material with uniform particle size distribution and fine particles. The two are ensured to be evenly mixed. A surfactant is added. The composite material is further processed and heated.

[0065] S3, post-processing and performance optimization:

[0066] (1) Heat treatment: The composite material is placed in a high-temperature furnace for heat treatment, and the temperature is generally controlled at 600°C to further stabilize its structure and improve cycle stability;

[0067] (2) Surface modification: The surface of the composite material is modified by chemical treatment to improve its wettability with the electrolyte and ion transfer efficiency;

[0068] (3) Performance testing: Conduct electrochemical performance testing on the prepared soft and hard carbon composite negative electrode materials, including evaluation of indicators such as specific capacity, cycle stability, and rate performance, and optimize and adjust the preparation process based on the test results.

[0069] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.

[0070] Effect Example

[0071] In the specific implementation, a variety of inactive cations such as Li, Mn, Ti, Sn, etc. are introduced, and the stoichiometric ratio of these inactive cations is precisely controlled to form a high entropy material. Then, the high entropy material is prepared into a negative electrode using a high-temperature solid phase method, and an electrochemical test is performed to evaluate the cycle performance and voltage attenuation of the negative electrode material, as shown in the following table:

[0072]

[0073] It can be seen from the above table that: soft carbon materials have larger carbon layer size and wider interlayer spacing, and exhibit excellent conductivity, while hard carbon materials have dense carbon layer structure and stable chemical properties, and excellent cycle performance. By adjusting the ratio of soft carbon and hard carbon, the comprehensive performance of the composite material can be optimized. The addition of soft carbon materials significantly improves the conductivity of the composite material and promotes the rapid transmission of electrons in the negative electrode material. The stable structure of the hard carbon material provides good support for the composite material, effectively preventing the structural collapse of the negative electrode material during charging and discharging, and extending the cycle life of the battery. The synergistic effect of soft and hard carbon composites makes it exhibit better electrochemical properties than single carbon materials in terms of specific capacity and rate performance.

[0074] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0075] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A composite negative electrode material for a sodium ion battery, which is composed of a soft carbon material and a hard carbon material in a certain proportion. Features: The precursor of the soft carbon material is selected from phenolic resin, an organic substance with high carbon content and easy to carbonize, and the precursor of the hard carbon material is selected from high molecular polymer, and the high molecular polymer is polyacrylonitrile.

2. A sodium ion battery composite negative electrode material according to claim 1, Features: The preparation method specifically comprises the following steps: S1. Material selection and pretreatment: (1) Soft carbon material precursor: Select phenolic resin with high carbon content and easy to carbonize organic matter as the precursor of soft carbon material. The precursor can form a soft carbon material with excellent conductivity during the carbonization process; (2) Precursor of hard carbon material: A high molecular weight polymer is selected as the precursor of the hard carbon material. After high temperature carbonization, the precursor can form a hard carbon material with stable structure and excellent cycle performance; (3) Pretreatment: Perform necessary pretreatment on the selected precursor, including cleaning, drying, crushing, etc., to ensure its purity and uniformity; S2. Carbonization and compounding: (1) Carbonization of soft carbon materials: The pretreated soft carbon material precursor is placed in a high-temperature furnace under inert atmosphere protection for carbonization treatment. The carbonization temperature is generally controlled at 600-1200°C. (2) Carbonization of hard carbon materials: The pretreated hard carbon material precursor is placed in a high-temperature furnace under inert atmosphere protection for carbonization treatment. The carbonization temperature is generally controlled at 900-1500°C. (3) Soft and hard carbon composite: the carbonized soft carbon material and the hard carbon material are mixed in a predetermined ratio, and physical methods such as ball milling and stirring are used in the mixing process. The ball milling speed is 200 to 500 r / min, and the ball milling time is 3 to 10 hours to obtain a matrix material with uniform particle size distribution and fine particles, and ensure that the two are evenly mixed. An appropriate amount of surfactant is added, and the composite material is further processed and heated; S3, post-processing and performance optimization: (1) Heat treatment: The composite material is placed in a high temperature furnace for heat treatment, and the temperature is generally controlled at 600-1200°C to further stabilize its structure and improve cycle stability; (2) Surface modification: The surface of the composite material is modified by chemical treatment to improve its wettability with the electrolyte and ion transfer efficiency; (3) Performance testing: Conduct electrochemical performance testing on the prepared soft and hard carbon composite negative electrode materials, including evaluation of indicators such as specific capacity, cycle stability, and rate performance, and optimize and adjust the preparation process based on the test results.

3. A method for preparing a composite negative electrode material for a sodium ion battery according to claim 2, Features: In S2(1), nitrogen is used as the inert atmosphere, and the specific carbonization temperature is adjusted according to the type of precursor and the required carbon layer size and interlayer spacing.

4. The method for preparing a composite negative electrode material for a sodium ion battery according to claim 2, Features: In S2(2), for the high molecular weight polymer precursor, its structural evolution during pyrolysis must also be considered to ensure that the final hard carbon material has the desired properties.

5. The method for preparing a composite negative electrode material for a sodium ion battery according to claim 2, Features: In the S2(3), the addition of a surfactant can improve the stability and dispersibility of the composite material, and the heating treatment is performed to optimize its electrochemical performance.

6. The method for preparing a composite negative electrode material for a sodium ion battery according to claim 2, Features: In S3(2), the chemical treatment method is acid washing or alkali washing.

7. A sodium ion battery, Features: The composite negative electrode material according to claim 1 is prepared by the preparation method according to any one of claims 2 to 6.